Xp21 DNA microdeletion syndrome in a Chinese family: clinical features show retinitis pigmentosa and chronic granuloma - Li, Mengyang; Hu, Xueqin; Wu, Xueli; Zhao, Na; Lian, Yuanyuan; Ma, Meijiao; Li, Huiping; Sheng, Xunlun (Frontiers in Genetics, 2024)
Xp21 DNA microdeletion syndrome is a very rare disease characterized by retinitis pigmentosa (RP), chronic granulomatous disease (CGD) and McLeod syndrome (MLS). The challenges remain yet in early diagnosis for many physicians due to the complex and diverse clinical manifestations. For the purpose of determining the pathogenic gene variants and definitive diagnosis in a patient medically backgrounded by RP and CGD from a normal Chinese family in this study, the whole exome sequencing (WES) was performed in such proband accordingly, and copy number variation (CNV) was further verified among other family members by qPCR. Genetic assessment revealed that the short arm of X chromosome in the proband had a deletion CNV Xp21.1p11.4(37431123-38186681) of approximately 0.755 Mb in size, and contained such three contiguous OMIM genes as X-link Kx blood group antigen (XK), cytochrome b-245 beta chain (CYBB), and RP GTPase regulator (RPGR). The qPCR results confirmed the copy number loss in Xp21.1p11.4 existing in the proband and his unaffected mother. According to the American College of Medical Genetics and Genomics (ACMG) guidelines for the CNV interpretation, the deletion of such segment was pathogenic variant. Our results provided the evidence that CNV deletion of Xp21.1p11.4 in the short arm of X chromosome was a pathogenic variant in such Chinese RP and CGD family, and McLeod phenotype was unavailable yet. This study implies that genetic testing is essential for a definitive diagnosis, which shall be of better assistance for physicians in prediction, diagnosis, genetic counseling and guidance for Xp21 DNA microdeletion syndrome.